World of popular entertainments : an edited volume of critical essays - Arrighi, Gillian.; Emeljanow, Victor. (Cambridge Scholars Pub., 2012)
"Despite the vibrant, complex, and ubiquitous nature of popular entertainments, the field has suffered from a lack of sustained academic attention. Nevertheless, popular entertainments have a global reach and a transnational significance at odds with the fact that the meaning and definition of both 'popular' and 'entertainment' remain widely contested. Since the late-nineteenth century, class-based prejudices in Western culture have championed the superiority of art and literature over the dubious and fleeting pleasures of 'entertainment.' Similarly, the term 'popular' has carried pejorative connotations, indicating something common and outside the conventional and highbrow productions of the purpose-built theatre house or concert hall"--Publisher.